PESAN KOMUNIKASI DALAM TRADISI AKKATERE DI DESA TANAH TOWA KECAMATAN KAJANG - Andriani, Riska; Farid, Muhammad; Kahar (KAGANGA KOMUNIKA: Journal of Communication Science, 2024)
The Akkatere tradition is an important ritual that is still carried out by the Ammatoa indigenous community in Tanah Towa Village, Kajang District, Bulukumba Regency. This ritual, which involves cutting a child's hair, is not only a symbolic manifestation of the journey of life, but also as a communication tool to convey social, spiritual and cultural messages that are very important in the life of indigenous communities. This research explores the communication messages contained in the implementation of the Akkatere tradition and how these messages strengthen social ties, culture and community identity. The research was conducted using a qualitative approach through direct observation and in-depth interviews with traditional leaders, stakeholders and families involved in this ritual. The research results show that the Akkatere tradition is a very effective communication medium in conveying values such as respect for ancestors, social solidarity, moral responsibility, and harmonious relationships between humans, nature and fellow community members. Keywords: Akkatere, Communication Message, Tradition, Ammatoa, Kajang, Cultural Symbolism.